(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This paper examines the linguistic and cultural challenges associated with the study and mutual translation of somatic phraseological units (SPUs) in English and Uzbek. SPUs—idioms involving body parts—are prevalent in both languages and often serve as expressions of emotion, character, and physical state. However, due to differences in cultural background and metaphorical thinking, their direct translation often leads to semantic distortion. This study investigates key strategies in translating these idioms accurately and highlights examples where literal and equivalent translations succeed or fail. The article presents theoretical ideas in this regard and proves them with examples.